Factor XI (P. T. A.) Deficiency with No Hemorrhagic Symptoms - Todd, Margaret; Wright, Irving S. (Thrombosis and Haemostasis, 1964)
A case has been presented, which has been diagnosed as a familial deficiency of Factor XI (PTA).The patient with Factor XI deficiency has a gross coagulation defect as demonstrated by numerous in vitro tests. However, to date neither the proband, his mother, nor his sister, who share the same deficiency, has shown any evidence of an abnormal bleeding tendency, even when subjected to repeated surgical procedures. These patients have a minor PTA deficiency and are heterozygous for the deficiency, which is transmitted as an autosomal recessive.